How Can Vaginal Birth Management Skills Gained Much Better? - KARAKOÇ, AYŞE; BAYRI BİNGÖL, FADİME; DEMİRGÖZ BAL, MELTEM (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective: In Turkey, midwives are given passive roles by claiming that the midwives are insufficient in the management of birth. The aim of this study was to determine the effects of clinical practice and simulation on normal birth management of midwifery students. Methods: The study was performed as a cross-sectional design at the Marmara University in Istanbul, Turkey, with 64 midwifery students. The data were collected via 2 questionnaires, the first for sociodemographic characteristics, the second for normal labor management skills. Results: The normal birth management skills of the students in the simulation group were significantly higher than those in the clinical group (P<0.05). The simulation group emphasized that a restricted case is the most significant disadvantage (87.5%). The clinical group students underlined that one-to-one contact with pregnant women is the most significant advantage (65.6%). Conclusion: It was seen that it is very advantageous to gain normal birth management skills firstly in simulation and then reinforce these skills in clinical practice in midwifery education. Thus, the disadvantages of both methods may be overcome.
Keywords: Simulation; labor management; midwifery; student; STUDENTS LEARNING-EXPERIENCES; MEDICAL-EDUCATION; SIMULATION; LABOR; CONFIDENCE; CONTINUITY